Load Frequency Control Investigation with Optimum PD-PID Controller with Derivative Filter - Jena, Tarakanta; Kumar Debnath, Manoj; Ranjan Padhi, Jyoti; Kumar Sanyal, Smaran (International Journal of Engineering and Technology, 2018)
Novel cascaded PD-PID controller with derivative filter (PD-PIDF) is projected in the present research work to investigate automatic generation control (AGC) in a dual area power system model comprising various generating sources. Each area of this dual area model consists of three different sources of generation namely hydro, gas and thermal unit. Moth Flame Optimization (MFO) technique is used as tuning tool for the projected PD-PIDF controller considering an abrupt power disturbance of 0.01p.u. in area 1. During the optimization process integral time absolute error is taken as cost/fitness function. The dynamic performance of the model is examined with three types of controllers namely, PID controller, cascaded PD-PID controller and cascaded PID controller with derivative filter. Also the supremacy of the projected PD-PIDF controller is validated over existing PD-PID and PID controller in view of various response based performance factors. Finally the robustness of the scrutinized model is verified by augmenting the nominal power loading of the control areas.Â